Short term culture with cAMP modulators before vitrification significantly improve actin integrity in bovine oocytes - Monteiro, Clara Ana Santos; Leal, Gabriela Ramos; Saraiva, Helena Fabiana Reis de Almeida; Garcia, Joaquim Mansano [UNESP]; Camargo, Agostinho Jorge dos Reis; Serapião, Raquel Varella; Nogueira, Luiz Altamiro Garcia; Rodrigues, André Luís Rios; Oliveira, Clara Slade (Elsevier, 2017)
Oocyte cryopreservation is a strategic tool for assisted reproduction, but has limited use due to the complex cellular structure of oocytes, which leads to sub-optimal survival rates. In this study, we used the SPOM in vitro maturation system, which is based on supplementation of cAMP modulators in order to extend meiotic arrest and improve oocyte maturation. cAMP modulators (Forskolin and IBMX) were administered in a short term culture (STC) before or after vitrification, followed by an extended maturation with cilostamide. We hypothesized that a STC with cAMP modulators would improve immature oocyte health and enhance cryotolerance. We found vitrification caused oocyte damage in a great extent, impairing nuclear maturation rates in all vitrified groups (Percentage of matured oocytes: CONT FRESH 77.8c; CONT VIT 31.4ab; STC/VIT 39.5b; VIT/STC 18.6a). Vitrification also promoted degradation of cytoskeletal actin filaments (Percentage of Injured oocytes: CONT FRESH 0.0a; CONT VIT 50.0b; STC/VIT 39.7b; VIT/STC 74.0c), and increased calcium release (Calcein-AM mean±SD: IMMATURE 1.0±0.49; VIT 1.76±1.13; STC 1.38±0.95; STC/VIT 1.58±0.99). However, STC seemed to attenuate negative effects of vitrification, since oocytes subjected to STC prior to vitrification presented predominance of polymerized actin filaments (Percentage of Intact oocytes). Unfortunately, embryo cleavage rate (SPOM 73.66a; STC/VIT 7.91b; VIT/STC 4.62b) and blastocyst development rate (SPOM 25.14a; STC/VIT 1.34b; VIT/STC 0.00b) was impaired in vitrified groups, regardless STC treatment. In conclusion, STC with cAMP modulators, Forskolin and IBMX, decreases cytoskeleton actin filaments injuries caused by oocyte vitrification, which may consequently increase oocyte viability. Our results suggest STC should be considered and improved for immature oocyte vitrification systems.
Keywords: Forskolin; IBMX; Pre-IVM; VG oocytes; Vitrification